Bifidobacterium compound preparations as a supplementary treatment for severe ischemic stroke: a systematic review and meta-analysis - Lu, Shenghua; Yu, Yunfeng; Liu, Yi; Zhang, Huimin; Liu, Rongzhen; Liu, Jianhe (Frontiers in Microbiology, 2025)
BackgroundThe benefits and risks of Bifidobacterium compound preparations (BCP) for patients with severe ischemic stroke (SIS) remain unclear. This study aimed to evaluate the efficacy and safety of BCP combined with enteral nutrition (EN) for SIS.MethodsEight databases were systematically searched for relevant literature up to January 1, 2025. Two researchers independently screened the records, extracted data, and assessed the risk of bias using the Cochrane Risk of Bias Tool 1.0 (RoB 1.0). Meta-analysis, sensitivity analyses, subgroup analyses, and publication bias assessments were conducted with RevMan 5.4 software.ResultsNine randomized controlled trials and 777 patients were included in the analysis. Meta-analysis showed that regarding nutritional status, compared with the EN group, the BCP combination group significantly increased albumin (mean difference [MD] = 4.55, 95% confidence interval [CI], 3.66 to 5.45, p < 0.00001), total protein (MD = 7.40, 95% CI 3.64 to 11.17, p = 0.0001), prealbumin (MD = 46.29, 95% CI 39.60 to 52.97, p < 0.00001), hemoglobin (MD = 10.26, 95% CI 8.09 to 12.43, p < 0.00001), and transferrin (MD = 0.67, 95% CI 0.32 to 1.03, p = 0.0002). Regarding neurological function, the BCP combination group significantly increased the Glasgow Coma Scale score (MD = 1.86, 95% CI 1.17 to 2.56, p < 0.00001) and decreased the National Institutes of Health Stroke Scale score (MD = −2.17, 95% CI −3.35 to −0.99, p = 0.0003). Regarding intestinal barrier function, the BCP combination group significantly reduced diamine oxidase (MD = −0.69, 95% CI −0.87 to −0.50, p < 0.00001) and D-lactate (MD = −0.09, 95% CI −0.11 to −0.08, p < 0.00001). Regarding immune function, the BCP combination group significantly increased IgA (MD = 0.50, 95% CI 0.36 to 0.63, p < 0.00001) and IgG (MD = 3.00, 95% CI 2.03 to 3.97, p < 0.00001). Safety analysis revealed that the BCP combination group significantly reduced the incidence of total adverse events (risk ratio [RR] = 0.28, 95% CI 0.13 to 0.62, p = 0.002), pulmonary infections (RR = 0.51, 95% CI 0.33 to 0.79, p = 0.003), reflux (RR = 0.21, 95% CI 0.05 to 0.92, p = 0.04), and diarrhea (RR = 0.28, 95% CI 0.12 to 0.67, p = 0.005).ConclusionBCP combined with EN can improve nutritional status, neurological function, intestinal barrier function, and immune function and reduce adverse events for patients with SIS. This approach represents a potential adjuvant treatment strategy for SIS.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420250653156, CRD420250653156.